(untitled) (Journal of the College of Basic Education, 2022)
In fractal compression the image to be encoded is partitioned into blocks called ranges. Each range is coded by reference to some other part of the image called domain and by some affine transformation parameters. The number of ranges plays an important rule in encoding parameters. In order to obtain high compression ratio, only a small number of blocks are allowed in encoding process. In this paper we suggested a new technique called Composed Partitioning Technique (CPT) to reduce the number of partitioning blocks with keeping as much as possible the quality of the reconstructed image. CPT is used the features of both quadtree and H-V techniques, it uses the uniformity criterion to decide the range block is to be partitioned or not, then it uses a criterion that depends on both the pixel and the edges information of the image to decide the type and the direction of the partitioning and this will give a more restriction to the partitioning process.